Legal Responsibility and Protection of Obstetrics and Gynecology Residents in Delegated Emergency Care Authority in Disadvantaged, Frontier, and Outermost Regions: An Analysis of Law No. 17 of 2023 on Health - Bahar Sangkur Gusasih; Ahmad Ma’mun Fikri (UNIVERSITAS PAKUAN, 2026)
Obstetric emergency services in Underdeveloped, Frontier, and Outermost (3T) regions face complex medicolegal challenges, particularly regarding the limited number of Obstetricians and Gynecologists (OBGYN). The presence of Residents (Specialist Doctor Education Program Participants/PPDS) assigned to 3T areas places them as emergency medical decision-makers through the mechanism of delegation of authority from the sole OBGYN as the Doctor in Charge of Services (DPJP). This study aims to analyze the boundaries of legal responsibility and protection for OBGYN Residents performing emergency obstetric procedures in 3T areas based on Law Number 17 of 2023 concerning Health. This study uses a normative juridical method with a statutory and conceptual approach. The results indicate that Law No. 17 of 2023 provides a framework for strengthening legal protection through medical personnel immunity in overmacht conditions within 3T regions. The study concludes that clear operational standardization of clinical delegation between educational institutions and regional hospitals is essential to ensure legal certainty and patient safety.